TINDAKAN PEMERINTAH MEMINIMALISIR TINGKAT KECELAKAAN BERLALULINTAS MASA PANDEMI COVID-19 - Joice Pangayow, Sherly (JOURNAL OF LAW AND NATION, 2024)
Humans are social creatures who have the right to develop themselves in meeting the needs of life so that in an increasingly modern era and all activities in travel are carried out quickly so that land transportation in the form of motorized vehicles is needed, in carrying out activities on the road often causes anxiety in the community because accidents often occur. The government has made regulations regarding traffic on the road to regulate and maintain order, safety and comfort in using the road, in carrying out these regulations requires law enforcement by the Government and public awareness of the law so as to create an orderly and safe traffic atmosphere. The approach taken in this study is to use a qualitative approach which uses empirical research methods, namely analyzing primary data or reality that occurs in the community and is supported by secondary data.